Chordophone revival in a collective instrument-making environment: the case of Mus.Mus.Cbr - Barão, Felipe (2023)
Christopher Small's (2012) concept of "musicking" challenges the traditional view of music-making by emphasizing the role of all individuals involved in a musical event, including musicians, audiences, and the stage crew. This perspective highlights the importance of social interactions in shaping the musical experience. This concept can also be applied to musical instrument makers. Hennion (2012) emphasizes the role of music as a powerful agent of social interactions, while Bates (2012) uses Actor-Network Theory (ANT) to explore the "social life of musical instruments," their unique stories, trajectories, and social relations. Rancier (2014) further underscores the ability of musical instruments to store information, memories and emotional associations with them. This paper presents an analysis of the case of students at a chordophone construction school based at the Associação Museu da Música de Coimbra (MUS.MUS.CBR.), considering the aforementioned perspectives. This school aims to revive traditional Portuguese chordophones, such as the viola toeira and guitarrinho/bandurrinho, and attracts students with varying backgrounds, gender, age, and professions, and promotes a sense of community through collaborative learning. The student's decision to participate in the instrument-making led to an exploration of their motivations, the nature of memories associated with the instruments, and the impact of the collective environment on the construction process. This ethnographic research aimed to analyze the social dynamics and memory storage involved in a communal context of musical instrument construction. The methodology used interviews with student builders and participant observation during the construction of a viola de arame. The study found that MUS.MUS.CBR.'s construction process fostered interaction among students, enabling them to imbue various forms of memory into their instruments. The instruments were distinct because they were created for personal use and designed to be played, and the communal environment of the school provided a dynamic and vibrant location for collective production.